Evaluasi Pelaksanaan Program Kursus Calon Pengantin (Suscatin) Di Kota Parepare - HS, Nur Ukhti; Majid, Makhrajani; Umar, Fitriani; Rusman, Ayu Dwi Putri; Usman, Usman (FAKULTAS ILMU KESEHATAN UNIVERSITAS MUHAMMADIYAH PAREPARE, 2026)
The high number of health problems related to reproduction, nutrition, and maternal mortality so that brides-to-be need knowledge preparation to get optimal health. The government issued preventive measures as a solution so that brides-to-be can understand the meaning of marriage and family health so that premarital education is carried out called the Bride-to-be Course (Suscatin). The purpose of this study is to evaluate the implementation of the suscatin program in Parepare City. This type of research uses descriptive qualitative. The informants were 15 people including the head of the KUA, suscatin educators, midwives, and brides-to-be by purposive and snowball sampling methods. This research was carried out in Parepare City including the KUA of West Bacukiki, KUA of Soreang, Lumpue Health Center and Cempae Health Center. The results implementation of the suscatin program in terms of human resources have been fulfilled but the infrastructure is not adequate due to the absence of suscatin independent space. Suscatin materials and methods have not complied with the rules applicable in the KUA. Premarital counseling is appropriate based on the procedures at the Puskesmas and is given in the form of a booklet or card of a healthy bride and groom, but not all brides-to-be come to participate in counseling. The suscatin program has not been fully implemented so it is recommended that relevant agencies need to increase cooperation and make rules that require brides-to-be to conduct premarital counseling at health centers, as well as for brides-to-be to follow counseling at the health center